To Increase Students' Interest In Physics By Using Modern Equipment And Laboratory Work - Shermurod Shamsiddinugli Isroilov (Genius Journals, 2023)
Improving the effectiveness of physics teaching is an urgent problem of today. An approach to assessing the acquisition of new physical knowledge, which is a system of criteria levels, where the transition to each subsequent level is possible only if the previous one is available. A method of teaching experimental activity to students in physics based on the implementation of the system-activity approach with the help of a school physical experiment is offered. The main thing is the activity of methodology students in mastering not only the content, but also the process of acquiring new knowledge.
Keywords: practical competence; cognitive; laboratory